CONTROL THE ONSET OF PUBERTY BY APPLICATION OF GONADOTROPIN RELEASING HORMONE (GNRH) IN IRAQI LAMB RAMS - Obaid , Mohammed Abed; Saleh , Wafir Mahdi (International Journal of Psychosocial Rehabilitation, 2020)
This study is design to investigate further the effect of two GnRH level treatments to onset of lamb-ram puberty and to minimize the incidence of sexual maturity age. Eighteen lamb-rams of 4-5 month of age with no previous history, body wt. around 14-17 kg, scrotal circumference around 8-10 cm, was conducted on this study which started from early November 2019 to the end of March 2020, at the animal yard of the Veterinary MedicineCollege - University of Baghdad- Al-Amerya state. Lamb-rams randomly divided into three groups; 1) Group (A) was treated with GESTAR (GnRH 0.00042g) 2ml/lamb/48 hs. 2) Group (B) was treated with GESTAR(GnRH 0.00042g)1ml/lamb/48 hs. 3) Group(C) was received nothing and stay as control group. All experimental lambs were received an equal quantities of food as 2kg of straw and 1 kg of oat and barely (grained). Testicular circumference, body wt. and hormonal analysis determined every 15 days. Results showed that; Testicular wt, of group of 2ml GnRH(A) 138.5±1.5g,group of 1ml GnRH( B) 190.0± 10.0g, and for control group(C) 96.5± 6.5g, Sc was of A) 25.5±0.5 cm, B) 29.75±0.75cm and C) 21.5±0.5, Testicular length was of A) 9.0±0.0 cm, B) 10.75±0.25cm and C) 7.25±0.25cm, testicular diameter was of A)5.05±0.05cm., B) 5.55±.05cm and C)3.5±0.1cm. testicular size was of A)140.0±0.0ml, B) 195.0±10.0ml and C)100.0±5.0ml, animal wt. was of A)37.5±1.5kg, B)42.0±3.0kg and C)36.0±1.0, testosterone level was of A)1.3±0.52ng/ml, B)2.12±0.74ng/ml and C)0.271±0.18ng/ml, estrogen level was of A) 5.81±0.38pg/ml, B) 11.63±3.7pg/ml and C)5.15±0.22pg/ml, volume of semen was of A) 0.675±0.04ml, B)0.90±0.04ml and C)0.60±0.04ml, mass motility was of A)75.0±2.04% , B)82.5±1.44% and C)65.0±2.04% ,individual motility was of A)78.75±1.25% ,B)86.25±1.25 and C)67.5±1.44 ,viability was of A) 81.0±1.29% ,B) 89.0±0.91% andC)70.0±1.82 and normal sperm was of A)80.5±2.1% ,B) 93.0±0.57% and C)71.25±1.54% . In conclusion 1ml Gestar (0,00042gm GnRH) is better in controlling and induction of puberty and sexual maturity in lamb-ram at 120 day treatment.